Dietary lycopene powder improves meat oxidative stability in Hu lambs. (9th October 2018) - Xu, Chenchen; Qu, Yanghua; Hopkins, David L; Liu, Ce; Wang, Bo; Gao, Yuefeng; Luo, Hailing
Abstract: BACKGROUND: The aim of this study was to evaluate the effect of dietary lycopene powder on meat quality and the oxidative stability of lipid and protein of longissimus thoracis (LT) in lamb. A total of 30 male lambs were randomly sampled from three feeding groups (control without lycopene supplement, 200 and 400 mg kg −1 lycopene powder respectively) after 3 months of feeding. The muscle samples were taken after slaughter and stored at 4 °C for 7 days. RESULTS: Compared with the control, the results showed that supplementation with lycopene powder gave a higher a * value (redness), and increased the levels of vitamin A and vitamin E. Increasing dietary lycopene powder resulted in a lower degree of lipid and protein oxidation, as evidenced by lower contents of thiobarbituric acid‐reactive substance and carbonyl compounds, and higher levels of sulfhydryl groups. CONCLUSION: Dietary lycopene powder is an effective antioxidant that blocks the oxidation of meat proteins and lipids, and has a positive effect on increasing lamb meat quality during storage. © 2018 Society of Chemical Industry